International Trade and Inclusive Growth : A Primer for Busy Policy Analysts - Lederman, Daniel (2012)
This note provides two analytical frameworks for understanding the role of trade in promoting inclusive growth in developing economies. A working definition of inclusive growth focuses on long-term, sustained growth associated with productivity growth and employment opportunities for broad portions of households and firms within countries. International integration can promote inclusive growth when workers and firms are able to adjust to enter into growing economic activities and adopt technologies availed through international trade. The frameworks described in this note build on simple household and firm choice models, which require only basic knowledge of development economics. The discussion highlights how these frameworks can help analysts focus on research and policy questions related to the impacts of international trade across the distribution of households and firms within countries. It also discusses publicly available data sets that can be used to explore some aspects of inclusive growth. In addition, the note highlights important caveats that need to be acknowledged by analysts and discusses avenues for future research, which needs to be part and parcel of the inclusive growth agenda.